Aetiologies of acute undifferentiated febrile illness at the emergency ward of the University of Gondar Hospital, Ethiopia. Issue 3 (24th January 2022) - Akelew, Yibeltal; Pareyn, Myrthe; Lemma, Mulualem; Negash, Markos; Bewket, Gezahegn; Derbew, Agegnehu; Belay, Gizeaddis; Pollmann, Julia; Adriaensen, Wim; Peeters, Marjan; Ombelet, Sien; Adane, Aynishet; et al.
Abstract: Objective: Causes of acute febrile illness (AFI) often remain undetermined in developing countries, due to overlap of symptoms and limited available diagnostics. We aimed to assess the aetiology of AFI in adults in a referral hospital in northwest Ethiopia. Methods: While all participants were tested for malaria by rapid diagnostic test (RDT), microscopy was only done on physician's request. Dengue virus (DENV) infections were detected using an RDT and ELISAs and dengue, yellow fever and chikungunya cases were identified by PCR. Bacterial aetiologies were investigated using blood culture and PCR. Results: The aetiology of acute infection was identified for 20.5% of 200 patients enrolled. Eleven percent tested positive for Plasmodium, while microscopy was only requested for half of the identified malaria cases. For 4.0% of the Plasmodium ‐infected patients, an acute or past DENV (co‐)infection was detected. We found 7.5% acute and 13.0% past DENV – all serotype 3 – infections. Bacterial infections were observed in 4.5% of the patients. Conclusion: Malaria is still a considerable aetiology of AFI and dengue is underrecognised. There are areas where both diseases occur concomitantly, and the DENV‐3 serotype presumably spreads from Sudan to northern Ethiopia. As only 20.5% of the aetiologies were identified, a broader testing platform is required.